一种高气液比产水气井临界携液流速预测方法 (2024)
一种高气液比产水气井临界携液流速预测方法，采用上限对数正态分布概率密度函数描述气井井筒内环雾流液滴尺寸分布，基于液滴的积累体积分布提出了特征液滴直径的概念，建立了更精确的液滴变形参数计算模型，基于特征液滴直径进行液滴变形和受力平衡分析，并结合液滴变形参数和曳力系数计算模型求解液滴受力平衡方程，最终实现气井临界携液流速的准确预测。本发明认为对于高气液比产水气井，采用基于统计学原理的上限对数概率密度函数描述气井井筒内的液滴尺寸分布更加符合气井实际条件，在此基础上提出特征液滴直径的概念并用于临界携液流速预测，比基于理论最大液滴直径的传统方法更加科学、合理，预测结果也更为准确、可靠。 The invention discloses a method for predicting the critical liquid-carrying flow velocity of a high-gas-liquid-ratio water production gas well. According to the method, the size distribution of annular fog flow liquid drops in a gas well shaft is described by adopting an upper limit logarithmic normal distribution probability density function; a concept of a characteristic droplet diameter is provided based on accumulated volume distribution of droplets; a more accurate droplet deformation parameter calculation model is established, droplet deformation and stress balance analysis is performedbased on the characteristic droplet diameter, a droplet stress balance equation is solved in combination with a droplet deformation